2002
DOI: 10.1093/protein/15.12.997
|View full text |Cite
|
Sign up to set email alerts
|

Domain swapping in ribonuclease T1 allows the acquisition of double-stranded activity

Abstract: A mutant of ribonuclease T1 (RNase T1), denoted RNase Talpha, that is designed to recognize double-stranded ribonucleic acid was created. RNase Talpha carries the structure of RNase T1 except for a part of its loop L3 domain, which has been swapped for a corresponding domain from alpha-sarcin. The RNase Talpha maintains the pleated beta-sheet structure and retains the guanyl-specific ribonuclease activity of the wild-type RNase T1. A steady-state kinetic study on the RNase Talpha-catalyzed transesterification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Interestingly, studies performed on the RNase T1 variant with an inserted loop 3 corresponding to α‐sarcin's sequence concluded that although a similar structure was observed to be retained in the mutant, changes in the modified loop 3 were observed, and loop 5 also appeared slightly distorted. In particular, loop 3 was displaced towards the surface of the molecule (Chen and Lin 2002). According to our results, it seems also that loop 3 and loop 5 are closely related and that modifications in one of them are somehow propagated to the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies performed on the RNase T1 variant with an inserted loop 3 corresponding to α‐sarcin's sequence concluded that although a similar structure was observed to be retained in the mutant, changes in the modified loop 3 were observed, and loop 5 also appeared slightly distorted. In particular, loop 3 was displaced towards the surface of the molecule (Chen and Lin 2002). According to our results, it seems also that loop 3 and loop 5 are closely related and that modifications in one of them are somehow propagated to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Inserting the targeting motifs of ribotoxins into other enzyme structures would allow the generation of specific targeted enzymes. In this sense, some groups have formed chimeric constructions, such as the insertion into the RNase T1 sequence of an α‐sarcin segment known to be essential in the ribosome recognition process (Chen and Lin 2002); in addition, several deletion mutants of restrictocin (Nayak et al 2000), α‐sarcin (Hwu et al 2000), and mitogillin (Kao and Davies 1999) were prepared to identify regions in fungal ribotoxins contributing to ribosome targeting and modulation of the catalytic activity. It was recently shown that the deletion of part of the long β‐hairpin in α‐sarcin produces an enzyme with interesting biological properties (García‐Ortega et al 2002): namely, the Δ(7‐22) mutant of α‐sarcin lacks the specific ability of the wild type to degrade rRNA in intact ribosomes and exhibits increased nonspecific ribonuclease activity and decreased interaction with lipid vesicles.…”
mentioning
confidence: 99%
“…They were annealed at 90°C for 3 min followed by cooling on ice. The transcription reaction was carried out at 37°C for 1 h under conditions as described previously ( 11 ). At the end of transcription, the transcript was heated to 90°C for 2 min in buffer and renatured by gradual overnight cooling to 4°C, which allowed the formation of a secondary structure that imitated the structure of TAR RNA.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of transcription, the transcript was heated to 90°C for 2 min in buffer and renatured by gradual overnight cooling to 4°C, which allowed the formation of a secondary structure that imitated the structure of TAR RNA. The 57-mer TAR RNA was 3′ end-labeled with cytidine 3′,5′-[α- 32 P]bisphosphate as previously described ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation